2021
DOI: 10.29333/ejmste/11403
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Effectiveness of STEAM Integrated Approach via Scratch on Computational Thinking

Abstract: This study examined the effectiveness of STEAM (Science, Technology, Engineering, Art, Mathematics) integrated approach via Scratch on five subconstructs of computational thinking (CT) among 29 male and 30 female students. A quasi-experimental design was employed in the research. The participants demonstrated the application of CT in designing games via Scratch during the intervention. The Computational Thinking Survey (CTS) was administered pre-CT and post-CT tests in measuring the five subconstructs of CT. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 63 publications
0
8
0
Order By: Relevance
“…Programming in education has been attracting the attention of researchers in the technology classroom [14,15], i.e., in the science [16,17] and mathematics classrooms [18,19]. One program that supports student programming is Scratch [20].…”
Section: Scratch In Mathematics Learningmentioning
confidence: 99%
See 1 more Smart Citation
“…Programming in education has been attracting the attention of researchers in the technology classroom [14,15], i.e., in the science [16,17] and mathematics classrooms [18,19]. One program that supports student programming is Scratch [20].…”
Section: Scratch In Mathematics Learningmentioning
confidence: 99%
“…Mai explained this by referring to how the points' coordinates in the first quadrant were positive numbers, while the zero was not a positive number [9]. In addition, some students (Ragad, Taleen, and Mai) appeared to conceive that (0, 100) laid in the Y-axis [14][15][16], while other students could not conceive that this point had a "place" in the Scratch stage [13,[17][18][19]. The teacher thought that the C1-C4 knowledge elements had critical roles in constructing C7.…”
mentioning
confidence: 99%
“…Based on several studies, STEM-based learning influences the development of computational thinking skills. In other words, this ability can be enhanced through STEM-based learning [14]- [17]. This shows that students' ability to combine science, technology, engineering and math skills is directly proportional to their computational thinking ability [18].…”
Section: Introductionmentioning
confidence: 98%
“…A growing number of studies investigated the implementation of CT in mathematics learning. Previous studies reported their findings on potential ways of integrating CT in mathematics learning, namely through the utilization of block-based programming languages (such as Scratch) (Rodríguez-Martínez et al, 2020;Tan et al, 2021), digital tools and algorithms (Abramovich, 2023), educational computer games (Soboleva et al, 2021), problem-solving modules rooted in CT (Subramaniam et al, 2023), and even through unplugged methods (Mumcu et al, 2023). As an emerging field, studies on CT are anticipated to escalate further, employing more varied approaches, methods, and topics (Chen et al, 2023).…”
Section: Introductionmentioning
confidence: 99%